The burden and predictors of late antenatal booking in a rural setting in Ghana - Charlotte Afful Oduro; Douglas Aninng Opoku; Joseph Osarfo; Adam Fuseini; Ama Asamaniwa Attua; Efua Owusu‐Ansah; Shamwill Issah; Augustine Barfi; Ephraim Foanor Kwadzodeh; Aliyu Mohammed (Wiley, 2023)
Abstract Aim The aim of the study was to determine the prevalence and key predictors of late booking among pregnant women accessing antenatal care services in a rural district of Ghana. Design Cross‐sectional study. Methods Data on demographic characteristics, knowledge of accessing antenatal care services and booking gestation were collected from 163 randomly selected pregnant women accessing accessing antenatal care in rural Ghana from 1 March 2022 to 30 April 2022 using a structured questionnaire. The chi‐square and logistic regression were used to explore associations between exposure and dependent variables. Results The prevalence of late accessing antenatal care booking among study participants was 44.8% (73/163). About 79.1% (129/163) of them had adequate knowledge of accessing antenatal care services. Maternal age of 35-49 years (AOR: 8.53, 95% CI: 2.41-30.12), participants whose partners had no formal education (AOR: 3.43, 95% CI: 1.03-11.39) and participants with adequate knowledge about accessing antenatal care services (AOR: 0.21, 95% CI: 0.07-0.62) were associated with late booking for accessing antenatal care services among study participants.